Lab-on-chip microfluidic impedance measurement for laminar flow ratio sensing and differential conductivity difference detection - Kong, Tian Fook (2017)
We present a microfluidic impedance device for achieving both the flow ratio sensing and the conductivity difference detection between sample stream and reference buffer. By using a flow focusing configuration, with the core flow having a higher conductivity sample than the sheath flow streams, the conductance of the device varies linearly with the flow ratio, with R2 > 0.999. On the other hand, by using deionized (DI)-water sheath flow as a reference, we can detect the difference in conductivity between the buffer of core flow and sheath DI-water with a high detection sensitivity of up to 1 nM of sodium chloride solution. Our study provides a promising approach for on-chip flow mixing characterization and bacteria detection.